Listeria Rhomboencephalitis in an Immunocompetent Host: Treatment With Trimethoprim-Sulfamethoxazole and Ampicillin. Issue 4 (July 2021) - Stavropoulos, Christine; Tolentino, Bryan; Woods, Krystina; Pyburn, Dewitt; Patterson, Shana; Jean, Raymonde
Abstract : Abstract: A 42-year-old healthy woman presented with fever and photophobia with rapid progression to diplopia, dysphonia, and tongue deviation. The cerebral spinal fluid had pleocytosis, but cerebrospinal fluid and blood cultures were negative. Cerebrospinal fluid polymerase chain reaction was positive for Listeria monocytogenes . Brain imaging was consistent with rhomboencephalitis. She was successfully treated with a combination of ampicillin plus trimethoprim-sulfamethoxazole. We present this case to highlight the syndrome of listeria rhomboencephalitis and the evolving treatment options.